2020
DOI: 10.1186/s12913-020-05932-w
|View full text |Cite
|
Sign up to set email alerts
|

Translation, cultural adaptation and psychometric properties of the Ghanaian language (Akan; Asante Twi) version of the Health Literacy Questionnaire

Abstract: Background Patients’ competencies and resources to manage their own health, which is termed health literacy, is a necessity for better health outcomes. Thus, it is relevant to have a comprehensive health literacy measurement tool suitable for populations of interest. The Health Literacy Questionnaire (HLQ) is a tool useful for health literacy assessment covering nine dimensions/scales of health literacy. The HLQ has been translated and validated in diverse contexts but has so far not been assessed in any count… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 32 publications
1
17
0
Order By: Relevance
“…The HLQ has been shown to have robust psychometric properties in its original version [ 21 , 22 ], as well as across European cultures [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ] and in some Asian and African cultures [ 32 , 33 , 34 ], supporting the initial nine-factor model and thus confirming its construct validity for use in a variety of settings. To allow assessment in communities and across specific populations with the aim of adaptation of services and structures to the health needs of people struggling with disease management or prevention, the HLQ has been translated and undergone validity testing in different countries and underlies the work done in the scope of the WHO National Health Literacy Demonstration Projects, in which Portugal is involved [ 10 ].…”
Section: Introductionmentioning
confidence: 76%
See 2 more Smart Citations
“…The HLQ has been shown to have robust psychometric properties in its original version [ 21 , 22 ], as well as across European cultures [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ] and in some Asian and African cultures [ 32 , 33 , 34 ], supporting the initial nine-factor model and thus confirming its construct validity for use in a variety of settings. To allow assessment in communities and across specific populations with the aim of adaptation of services and structures to the health needs of people struggling with disease management or prevention, the HLQ has been translated and undergone validity testing in different countries and underlies the work done in the scope of the WHO National Health Literacy Demonstration Projects, in which Portugal is involved [ 10 ].…”
Section: Introductionmentioning
confidence: 76%
“…They considered that “the range of conditions studied here, sample sizes exceeding N ≥ 300 are most likely to ensure adequate convergence of the robust WLS estimator, accurate recovery of factor loadings and covariances, and satisfactory approximation of standard errors and the (chi-square) statistic. Thus, we considered a sample > 300 ensure a robust analysis with WLSMV that provides accurate estimates of all the information from the factor analysis” [ 33 ]. Eligible participants were clinic attendees aged 18 or older with a diagnosis of diabetes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The development and publication of validity evidence has not kept pace with the application of the HLQ in practice. However, since the literature review for this study was conducted, more articles presenting evidence for the HLQ have been published [ 1 , 2 , 11 , 13 , 21 , 66 , 73 , 89 , 96 , 107 , 108 ].…”
Section: Discussionmentioning
confidence: 99%
“…The nine domains of the HLQ are designed to measure the experiences people have when they engage in understanding, accessing and using health information and health services. In its development context, the HLQ was found to have strong construct validity, reliability and acceptability to clients and clinicians [ 30 , 35 ] and confirmatory factor analysis (CFA) has found that the items and scales in HLQ translations tend to behave in comparable ways to the English-language HLQ [ 36 , 37 , 38 , 39 ], even among disparate groups in low-resource settings [ 40 , 41 , 42 ]. HLQ data are used in pre-post evaluations and to develop profiles of health literacy strengths and needs to describe the health literacy of individuals and whole populations [ 12 , 43 ].…”
Section: Introductionmentioning
confidence: 99%